Commercial Aspects and Market Pull of Biosensors in Diagnostic Industries - Kumar A.; Mahato K.; Purohit B.; Chandra P. (My University, 2025)
The extensive advancements in the micro-manufacturing process have led to the development of enormous miniaturized technologies for personalized care and health management. Several technologies have been reported for saving the environment and food from getting spoiled based on miniaturized devices across the globe. Moreover, the growth of the biosensor industry has tremendously affected the market pull of sensing devices around the world. In this chapter, we have discussed various such aspects of the biosensor development process in context to their mass manufacturing feasibilities and their commercial aspects. Herein, we have also discussed limitations and various challenges associated with the miniaturized biosensors in terms of commercial acceptance. Apart from this, we also provide the SWOT (strengths, weaknesses, opportunities, and threats) analysis of the various types of contemporary biosensors. © The Editor(s) (if applicable) and The Author(s), under exclusive licence to Springer Nature Singapore Pte Ltd. 2022.